Influence of Br−/S2− site-exchange on Li diffusion mechanism in Li6PS5Br: a computational study. (29th November 2021) - Sadowski, Marcel; Albe, Karsten
Abstract : We investigate how low degrees of Br − / S 2 − site-exchange influence the Li + diffusion in the argyrodite-type solid electrolyte Li 6 PS 5 Br by ab initio molecular dynamics simulations. Based on the atomic trajectories of the defect-free material, a new mechanism for the internal Li + reorganization within the Li + cages around the 4 d sites is identified. This reorganization mechanism is highly concerted and cannot be described by just one rotation axis. Simulations with Br − / S 2 − defects reveal that Li + interstitials (L ii . ) are the dominant mobile charge carriers and originate from Frenkel pairs. These are formed because B rS . defects on the 4 d sites donate one or even two L ii . to the neighbouring cages. The L ii . then carry out intercage jumps via interstitial and interstitialcy mechanisms. With that, one single B rS . defect enables Li + diffusion over an extended spatial area explaining why low degrees of site-exchange are sufficient to trigger superionic conduction. The vacant sites of the Frenkel pairs, namely V Li ′, are mostly immobile and bound to the B rS . defect. Because S Br ′ defects on 4 a sites act as sinks for L ii . they seem to be beneficial only for the local Li + transport. In their vicinity T4 tetrahedral sites start to get occupied. Because the Li + transport was found to be rather confined if S Br ′ and B rS . defects are direct neighbours, their relative arrangement seems to be crucial for effective long-range transport. This article is part of the Theo Murphy meeting issue 'Understanding fast-ion conduction in solid electrolytes'.